Analysis of Factors Affecting Parenting on the Incidence of Sibling Rivalry in Children Aged 3-6 Years in Batang Ayumi Julu Village, North Padang Sidempuan - Harahap, Annisar; Suroyo, Razia Begum; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2024)
Sibling rivalry is a problem that affects children's development due to the gap between siblings. This research aims to determine the factors that influence parenting patterns on the incidence of sibling rivalry in children aged 3-6 years. The research design uses a quantitative and qualitative approach (mixed method) with a cross-sectional approach. The research population was mothers who had children aged 3-6 years in Ward I, Batang Ayumi Julu District, Padangsidempuan. The research results show that there is an influence of authoritarian, democratic, permissive, and passive parenting on the incidence of sibling rivalry, with passive parenting as the most dominant factor. It is recommended for parents, especially mothers, to involve and interact with siblings in daily life to avoid sibling rivalry.